Evidence of validity of the work tasks motivation scale for teacher - Inácio, Amanda Lays Monteiro [UNESP]; Mariano, Maria Luzia Silva; Bzuneck, José Aloyseo (University of Minho, 2023)
This study aimed to estimate validity indicators based on the internal structure and accuracy of The Work Tasks Motivation Scale for Teacher by using a Confirmatory Factor Analysis (CFA). The study was attended by 452 teachers from different stages, educational institutions, and regions of Brazil. The results from CFA indicated the presence of the four motivational dimensions, as reported in the scientific literature, with internal consistency indices considered acceptable and good fit indices for the instrument. There were significant correlations between the factors, both positive and negative. Finally, teachers proved to be more autonomously motivated. The results highlight important contributions to the psychoeducational area, with well-developed psychometric indicators of the instrument for the evaluation of the motivational construct related to the teaching work.
Evidencia de validez de la escala de motivación laboral docente
Evidências de validade da escala de motivação de professores para o trabalho
Keywords: Confirmatory factor analysis; Self-Determination Theory; Teacher Motivation; Teaching